Continuous and interrupted abdominal-wall closure after primary emergency midline laparotomy (CONIAC-trial): study protocol for a randomised controlled single centre trial. Issue 11 (23rd November 2022) - Wolf, Sebastian; Arbona de Gracia, Luis; Sommer, Florian; Schrempf, Matthias Christian; Anthuber, Matthias; Vlasenko, Dmytro
Abstract : Introduction: The optimal closure of the abdominal wall after emergency midline laparotomy is still a matter of debate due to lack of evidence. Although closure of the fascia using a continuous, all-layer suture technique with slowly absorbable monofilament material is common, complications like burst abdomen and hernia are frequent. Methods and analysis: This randomised controlled trial with a 1:1 allocation evaluates the efficacy and safety of a continuous suture with or without additional interrupted retention sutures for closure of the abdominal fascia. Patients with an indication for a primary emergency midline laparotomy are eligible to participate in this study and will be randomised intraoperatively via block randomisation. Fascia closure in the intervention group will be done with a standard continuous suture with slowly absorbable monofilament material (MonoMax 1, B. Braun, Tuttlingen, Germany) and additional interrupted retention sutures every 2 cm of the fascia using rapidly absorbable braided material (Vicryl 2, Ethicon, Norderstedt, Germany). In the control group, the fascia is closed only with the standard continuous suture with slowly absorbable monofilament material. Sample size calculations (n=111 per study arm) are based on the available literature. The primary endpoint is the rate of dehiscence of the abdominal fascia (rate of burst abdomen within 30 days or rate of incisional hernia within 12 months). Secondary endpoints are wound infections, quality of life, length of hospital stay, morbidity and mortality. Patients as well as individuals involved in data collection, endpoint assessment, data analysis and quality of life assessment will be blinded. Ethics and dissemination: The study protocol, the patient information and the informed consent form have been approved by the ethics committee of the Ludwig-Maximilians-University, Munich, Germany (reference number: 20-1041). Study findings will be submitted for publication in peer-reviewed journals. Trial registration number: DRKS00024802. WHO universal trial number: U1111-1259-1956